An improved 3D microstructure reconstruction approach for porous media. (1st January 2023) - Li, Kai-Qi; Liu, Yong; Yin, Zhen-Yu
Abstract: Microstructure reconstruction of porous media is vital for the evaluation of material properties, which has been applied in many fields. Various approaches have been proposed for the reconstruction modeling of porous media. However, most of them considered the porous medium as an ideal two-phase material, and little attention is paid to the isolated solid clusters among pore domains. Porous media with solid isolations are inconsistent with actual structures and are likely to result in computational errors when determining the transport properties. Aiming to address this issue, an efficient approach to reconstruct the microstructure of porous media is proposed, which utilizes the watershed algorithm to identify and eliminate the isolated solid clusters. In addition, several morphological descriptors, including Minkowski functions, pore size distribution and permeability, are involved in measuring the discrepancies between target structures and reconstructions. Results demonstrated that the proposed method rebuilds microstructures without isolations from two-dimension images or autocorrelation functions and preserves valuable morphological information within the microstructures. By means of a simple workflow, the proposed method can be employed to reconstruct porous media without isolated solids and applied to investigate the transport mechanisms of porous media. Graphical abstract: Image, graphical abstract